Information Technology Literacy and Intention to Use Fintech in Micro Business Enterprise: The Moderating Role of Perceived Security - Haryanto, M. Y. Dedi; Sarsiti, Sarsiti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The Fintech phenomenon is the delivery of financial products and services via the synthesis of technological platforms and innovative business models. Intention to use Fintech for business processes largely remains unexplored in the context of Micro Small and Medium Enterprise (MSME). Responden of this study are 130 owner of MSMEs in Palembang city, one of the provincial capitals in Indonesia. Data was collected with questionair using a field survey. The method applied for data analysis was partial least squares structural equation modeling (PLS-SEM). The result show that technology literacy are not associated with and intention to use fintech. However, other result confirm that perceived security has a moderating effect on the relation between technology literacy and intention to use fintech. This is consistent with the argument that small business owner assess the security of fintech firm taking into account in adopting fintech services. Keyword: Information technology literacy, Intension to use, Financial technology, Perceived security.